2012
DOI: 10.1007/s12325-012-0018-8
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Moxifloxacin-Dexamethasone Eyedrops as Treatment for Bacterial Ocular Infection Associated with Bacterial Blepharitis

Abstract: The fixed-dose combination of moxifloxacin, 0.5% and dexamethasone, 0.1% was therapeutically equivalent and as well tolerated as the concomitant dosage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Another antibiotic-steroid combination, moxifloxacin plus dexamethasone, was shown to produce clinical improvement in patients with bacterial blepharitis. 15 The risk of elevated IOP is a concern with ocular steroid administration, especially when used for extended periods of time. In the two source studies upon which the current analysis was based, marked differences were observed in the magnitude of IOP change in the US and Chinese populations, and for this reason, IOP findings were not pooled.…”
Section: Discussionmentioning
confidence: 99%
“…Another antibiotic-steroid combination, moxifloxacin plus dexamethasone, was shown to produce clinical improvement in patients with bacterial blepharitis. 15 The risk of elevated IOP is a concern with ocular steroid administration, especially when used for extended periods of time. In the two source studies upon which the current analysis was based, marked differences were observed in the magnitude of IOP change in the US and Chinese populations, and for this reason, IOP findings were not pooled.…”
Section: Discussionmentioning
confidence: 99%
“…Prolongation of viral shedding following monotherapy with corticosteroids has been reported; [50] however, combination therapies with corticosteroids and anti-infective agents (i.e., antibiotics) have proven to be effective in treating viral and bacterial conjunctivitis. [51,52] Ophthalmic formulations of PVP-I/dexamethasone are widely investigated. PVP-I 0.4%/dexamethasone 0.1% suspension, PVP-I 1.0%/dexamethasone 0.1%, and PVP-I 0.6%/dexamethasone 0.1% have been used, and the results suggest that the combination therapies reduce patient symptoms and eradicate the virus effectively.…”
Section: Adenoviral Conjunctivitismentioning
confidence: 99%
“…Fluoroquinolones such as ciprofl oxacin ophthalmic solution 0.3 % and topical levofl oxacin 0.5 % proved their effi cacy in the management of bacterial blepharitis [ 18 -20 ]. The fourth-generation fl uoroquinolones are also used for the treatment of bacterial blepharitis [ 21 ]. Corticosteroid-antibiotic combinations are also available in either ointment or eyedrop form [ 22 , 23 ].…”
Section: Bacterial Blepharitismentioning
confidence: 99%